2021
DOI: 10.1016/j.heliyon.2021.e07124
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensionality of inter-parental conflict on aggression and mental health among adolescents

Abstract: The research sets out to reveal that multidimensionality of inter-parental conflict is a limitation in the direction of research which suggests that inter-parental conflict is a risk factor to poor mental health and aggression in adolescents. To validate the above assertion, 394 adolescents (227 males; mean age = 15.6, SD = 1.74) were purposively sampled for the study. Two hypotheses were formulated and tested and data were analyzed using the multiple regression analysis and Multivariate Analysis of Variance/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For the parent/carer, the lengthy waiting times for access to the specialist provision required to support vulnerable children require further investigation. The behavioural responses that are associated with a child with an NDD can often create challenging environments for the parent/carer and wider family (Harold, et al., 2013; Olatunji and Idemudia, 2021). Lastly, but more importantly, the study highlights significant questions for further exploration into the future overall well-being of the LAC who has been diagnosed with an NDD or has a suspected NDD.…”
Section: Discussionmentioning
confidence: 99%
“…For the parent/carer, the lengthy waiting times for access to the specialist provision required to support vulnerable children require further investigation. The behavioural responses that are associated with a child with an NDD can often create challenging environments for the parent/carer and wider family (Harold, et al., 2013; Olatunji and Idemudia, 2021). Lastly, but more importantly, the study highlights significant questions for further exploration into the future overall well-being of the LAC who has been diagnosed with an NDD or has a suspected NDD.…”
Section: Discussionmentioning
confidence: 99%
“…Kondisi ini diduga tidak terlepas dari faktor riwayat lingkungan keluarga. Ibu pada keluarga besar cenderung mendapat campur tangan orang tua/mertua serta dari anggota keluarga lainnya terkait dengan urusan rumah tangga maupun pola asuh terhadap anak, partisipasi atau keterlibatan yang berlebihan dari anggota keluarga lain yang memicu konflik dapat menyebabkan stres emosional ibu pada keluarga besar (Andayani, 2000;Hsieh dkk., 2009;Olatunji & Idemudia, 2021;Onwuasoanya, 2006;Sevigny & Loutzenhiser, 2009;Haryanti & Sumarno (2014)). Dibutuhkan efikasi diri dalam pengasuhan tinggi agar kesejahteraan anak dapat terjaga (Salo dkk., 2022).…”
Section: Pendahuluanunclassified
“…In a family that emphasizes strong personality grows, children grow comfortably and have selfworth (Shek et al, 2021). Psychological well-being of adolescents is present in families that emphasize warmth and positive character building in their homes (Cooper et al, 2019;Golombok et al, 2017;Olatunji & Idemudia, 2021). On the other hand, adolescents who show low self-esteem and lack of harmony in their relationships are more often found in families with poorer character education (Olatunji & Idemudia, 2021;Saurabh & Ranjan, 2020).…”
Section: Significance Of Studymentioning
confidence: 99%
“…Psychological well-being of adolescents is present in families that emphasize warmth and positive character building in their homes (Cooper et al, 2019;Golombok et al, 2017;Olatunji & Idemudia, 2021). On the other hand, adolescents who show low self-esteem and lack of harmony in their relationships are more often found in families with poorer character education (Olatunji & Idemudia, 2021;Saurabh & Ranjan, 2020). Some studies (Angelhoff et al, 2021;García et al, 2019) found that adolescents with antisocial and withdrawal behavior because of low self-esteem tend to have problems in social life (Garcia et al, 2020;Martínez et al, 2021).…”
Section: Significance Of Studymentioning
confidence: 99%